Enhancement of alkaline water splitting activity by Co–P coating on a copper oxide nanowire. Issue 3 (18th December 2018) - Chang, Bing; Yang, Yingchun; Ye, Zhixiang; Liu, Shengyu
Abstract : An amorphous Co–P shell coating on a copper oxide nanowire array to synergistically boost the catalytic activity toward alkaline water splitting, and this shell/core Co–P/CuO nanowire array is durable with a cell voltage of only 1.645 V to reach 20 mA cm −2 by a two-electrode configuration in an alkaline water electrolyzer. Abstract : Hydrogen is the most attractive source of energy in the 21 st century. However, high-efficiency mass production of hydrogen still faces many challenges. Although electrochemical water splitting is an ideal way to produce hydrogen, it requires low-cost and efficient electrocatalysts. In this work, a hybrid shell/core Co–P/CuO nanowire array was fabricated by Co–P film electrodeposition on a CuO nanowire array. Because of the synergy between Co–P and CuO nanowire arrays, Co–P/CuO shows remarkable activity toward the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). This bifunctional electrocatalyst achieving 20 mA cm −2 requires a cell voltage of only 1.645 V, and has superb long-term electrochemical stability and high faradaic efficiency.